Pengalaman Lansia tentang Kebutuhan Layanan Kesehatan pada Pos Pelayanan Terpadu: Studi Fenomenologi - Eliyana, Eliyana; Ardiyanti, Yulia (Universitas Faletehan, 2023)
The rise of elderly number poses a challenge for many nations worldwide, particularly developing countries such as Indonesia. The presence of elderly integrated health post could serve as a supportive facility for elderly healthcare at community level. The optimal health services provided at integrated health post can contribute to the improvement of elderly’s wellbeing. This research aimed to explore the elderly's experiences of the necessity of health services in the Elderly Integrated Health Post of Patebon II Kendal Public Health Center. A qualitative approach with phenomenological approach was used in this study. The data collection was done by using semi-structured in-depth interviews to 10 elders lasting between 45-60 minutes. To ensure trustworthiness, member checking and peer-review were conducted on all interview transcripts before the process of data analysis by qualitative thematic analysis. This study found four major themes, namely: health care experiences, not diverse integrated health post service, efficiency of services, and health provider characteristic. The elders stated that they were unable to meet all their health needs. The integrated health post must offer comprehensive services, including psychological, social, and spiritual needs, not only focusing on their physical needs. Thus, the services can have a positive impact on the improvement of elderly quality of life.